Análise da produção do cuidado nos CAPS de João Pessoa a partir de indicadores de atenção psicossocial - Maia, Michelle Grace Florentino (2023)
The Psychiatric Reform in Brazil has promoted a significant change in mental health care, prioritizing dehospitalization and community care, making psychosocial care centers (CAPS) fundamental in this new model of care. CAPS are open communitybased services that operate from the perspective of the psychosocial care model. In this, the object of work is the subject in psychological distress, considering their political, historical and sociocultural constitution, choosing the territory as a space for the production of care, through intersectoral, social and support networks. Considering the importance of CAPS in the context of implementing the psychosocial care model and considering the evaluation of services as a fundamental element of SUS planning and management, this work aims to evaluate the production of care in CAPS III in the city of João Pessoa -PB. This is a descriptive study with a quantitative approach based on documentary analysis. CAPS Caminhar, CAPS Gutemberg Botelho and CAPS AD Jovem Cidadão were included in the study. Data collection took place between December 2022 and April 2023 with a time frame from July to December 2022. 2,664 medical records were analyzed, eight nursing shift books, seven multidisciplinary team shift books, two collective activity books, five team meeting books, a book of referrals to other services and an admission book. Sixteen mental health indicators were selected in a participatory survey of CAPS III workers and managers in the Southeast region. The indicators have a ratio calculation methodology, analyzing eight dimensions of psychosocial care with a monthly, quarterly, biannual or annual time frame. The data was analyzed using the Excel program, using descriptive statistics, presenting the results in the form of relative frequencies (medians, minimum and maximum). The results show that the services are able to respond locally to crisis situations, with a low percentage of referrals to psychiatric emergencies (4.8%); the team's commitment to continuously qualifying its group practices is relatively successful (40.1%). The formulation (20.9%) and review of singular therapeutic projects (6.6%) and intersectoral work (5.5%) take place in the services, but in an insufficient and limited way. Among the weaknesses identified are the lack of clinicalinstitutional supervision, low participation of family members in family groups (0.9%) and insufficient therapeutic offers to users' family members during crisis situations (6.3%). The indicators of user adherence to medication, inclusion of users with intellectual disabilities, participation of managers and continuing education were not possible to analyze. The conclusion is that the CAPS operate from the perspective of the psychosocial paradigm, with some limitations, and that the set of mental health indicators studied make a positive contribution to analyzing the production of mental health care, and can be used in the day-to-day running of the services as a strategy for evaluating the work process by the workers and managers themselves.